Age Related Changes in Body Weight and Gonadal Size in Jersey x Kankrej Crossbreds From Birth to Puberty - SINGH, S K; LAISHRAM,; PATEL, J M (The Indian Journal of Animal Reproduction, 2023)
Gonadal growth relative to age and body weight changes was studied in 40 Jersey X Kankrej crossbred male calves by collecting testes at different ages starting from birth to 16 months of age. Paired testicular weight (PTW) at birth was 4.52±0.92 gm which increase to 16.77±2.19 to 38.43±9.55 gm at 5 and 8month of age. Thereafter it grew rapidly and attained 107.67 ±23.90 and 442.80±41.46 gm at 12 and 16 month of age respectively. Thelength, width, thickness and circumference of testes showed steady growth indicating constantshape. Highly significant (P < 0.01) and positive correlation of age and body weight with PTWand other testicular biometrics were recorded.Equation for predicting PTW and testicular circumference from age and body weight havebeen developed.
Keywords: Body Weight; Gonadal Size; Jersey; Kankrej; Puberty; Age Related Changes